Shoulder injuries in collegiate baseball athlete during 2023-2024 - Mercado, Efril Ian V. 2001-; Papa, Emmanuel V. (Quezon City College of Human Kinetics, University of the Philippines Diliman, 2025)
Baseball-related overhead activities are known to be a cause of shoulder injuries that affect athletes in the sport. The aim of this study is to determine the incidence and various types of shoulder injuries that are common to collegiate baseball athletes in the 2023 and 2024 seasons and their positional association. 14 pitchers, 21 infielders, 11 outfielders, and 8 catchers took part in the study. The goal was to determine the rate of shoulder injuries, the differences between rates by season, and the characteristics of specifically position-strain injuries. The particular type of quantitative research applied in the study was the survey-based method. Participants were required to fill out a structured questionnaire pertaining to their demographic information, playing career, and history of previous injuries. The variable analysis of the data was done with descriptive statistics methods with regards to the type of injury and positional injury frequency. Out of the 54 participants, 43% of them claimed to have shoulder injuries, rising slightly in 2024 over the 2023 season. Out of all these, the most frequent were the strains and overuse injuries, with a percentage of 34.78%, and the sprains followed at 30.44%. Players in infield positions had a high proportion of incidence and complaint compared with pitcher, outfielder, and catcher positions. Additionally, as shown in the study, infielders and pitchers are most likely to get shoulder injuries since their movements necessitate overhead motions repeatedly. Altogether, the findings speak for proper workload handling, effective biomechanics, and tailored conditioning schedules as effective ways of minimizing injury hazards. The main recommendations are for the coaches, trainers, and sports administrators for preventing a recurrence of the injuries, such as conducting a screening of an athlete before the beginning of the season, ensuring that the athlete has the right regimen, and implementing a proper structured recovery regimen.
Thesis (Bachelor of Sports Science)-University of the Philippines Diliman
Includes bibliographies
Keywords: Shoulder -- Wound and injuries; Baseball; College athletes